Coronary venous lipid peroxide concentrations after coronary angioplasty: correlation with biochemical and electrocardiographic evidence of myocardial ischaemia. Issue 7 (July 1992) - Oldroyd, K G; Paterson, J R; Rumley, A G; Eteiba, H; Rae, A P; Shepherd, J; Cobbe, S M; Hutton, I
Abstract : Background —Raised lipid peroxide concentrations in coronary venous plasma have been reported after coronary angioplasty in humans. This may reflect increased free radical activity after myocardial ischaemia and reperfusion. If so, it may be possible to correlate lipid peroxide concentrations with the degree of myocardial ischaemia produced during angioplasty. Methods —15 patients (age range 42-70; 12 men) with stable angina pectoris undergoing angioplasty of a proximal left anterior descending coronary artery stenosis were studied. Plasma lipid peroxide and lactate concentrations were measured in sequential blood samples taken from the great cardiac vein before and immediately after one to five serial 60 second balloon inflations. The maximum ST segment shift during each balloon inflation was also measured. Results —Lipid peroxide concentrations in coronary venous plasma were raised from pre-angioplasty values by more than 2 SDs of the relevant measurement error after 27 out of 46 (59%) balloon inflations. Lactate concentrations were raised after 43 out of 46 (93%) balloon inflations. No significant difference was found between the peak percentage change of either lipid peroxide or lactate concentrations after any of the first three serial inflations. The maximum ST segment shift after each of the first three serial inflations was also similar. Coronary venous lactate concentrations after balloon inflation correlated positively with the maximum ST segment shift, but did not correlate with lipid peroxide concentrations. Conclusions —Raised lipid peroxide concentrations in coronary venous plasma can be detected in humans after balloon angioplasty. There is no positive correlation between lipid peroxide concentrations in coronary venous plasma after angioplasty and the degree of preceding myocardial ischaemia as assessed by either ST segment shift or lactate production. These indices showed that one to three serial 60 second balloon inflations each produce a similar degree of myocardial ischaemia. The origin of the raised lipid peroxide concentrations in coronary venous plasma after angioplasty remains unknown.